2015
DOI: 10.2340/00015555-1939
|View full text |Cite
|
Sign up to set email alerts
|

Positive Changes in Self-management and Disease Severity Following Climate Therapy in People with Psoriasis

Abstract: The aim of this study was to investigate the impact of climate therapy on self-management in people with psoriasis. This was a prospective study of 254 adults with chronic psoriasis who participated in a 3-week climate therapy (CT) programme. The 8-scale Health Education Impact Questionnaire (heiQ) was completed at baseline, after 3 weeks of CT, and 3 months later. Change was assessed using paired sample t-tests mean (95% confidence interval) change scores (range 1-4). All heiQ scales showed statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
(34 reference statements)
0
23
1
2
Order By: Relevance
“…The final instrument has eight scales, which have been translated and culturally adapted into over 20 languages, and are currently being applied in clinical trials worldwide, including in Norway [12][13][14][15]. However, only a few studies have reported the psychometric performance of the heiQ in the diverse settings, in which it is being applied [16][17][18][19][20][21][22].…”
Section: Making Robust Decisions About the Impact Of Health Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The final instrument has eight scales, which have been translated and culturally adapted into over 20 languages, and are currently being applied in clinical trials worldwide, including in Norway [12][13][14][15]. However, only a few studies have reported the psychometric performance of the heiQ in the diverse settings, in which it is being applied [16][17][18][19][20][21][22].…”
Section: Making Robust Decisions About the Impact Of Health Educationmentioning
confidence: 99%
“…This builds up the nomothetic web around the questionnaire and self-management across settings, and should give researchers, program implementers and policymakers the confidence that the heiQ will deliver reliable information on program outcomes and will support quality improvement activities. The heiQ has revealed effects in studies with different health care programs [e.g 14,15], and this is likely due to the scales being sensitive to meaningful and relevant outcomes for people participating in self-management programs. …”
Section: Practice Implicationsmentioning
confidence: 99%
“…In our past study HT was regarded cost-effective for the high indirect costs only for patients with severe psoriasis (29). Similar to the Norwegian study (25) we were unable to confirm longterm improvement of QoL in PS patients (25).…”
Section: Discussionmentioning
confidence: 49%
“…New courses run by the patient organisations focus more on empowerment than clearance of the disease. Wahl et al (25) studied the effect of climate therapy on self-management in PS patients, and our study focused also on AD patients showing that both PS and AD were statistically significantly improved (25). In our past study HT was regarded cost-effective for the high indirect costs only for patients with severe psoriasis (29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation